Boom Clay pore water geochemistry at the Mol site: Experimental data as determined by in situ sampling of the piezometers. (January 2022) - Honty, Miroslav; Frederickx, Lander; Wang, Lian; De Craen, Mieke; Thomas, Peter; Moors, Hugo; Jacops, Elke
Abstract: In many countries, geological disposal in clay is the primary option for the final disposal of high-level radioactive waste and spent fuel. In Belgium, the Boom Clay is studied as a potential host rock for the disposal of radioactive waste. In this frame, the pore water geochemistry of the Boom Clay is an essential feature for evaluating the performance and long term safety of geological disposal in a host rock because: (1) it determines the speciation and solubility of radionuclides, and (2) it is required as initial or boundary condition to evaluate the interactions with other repository components, i.e. the different waste forms and the engineered barrier system ( e.g. overpack materials, backfill), as well as to evaluate the influence of the repository construction ( e.g. oxidation, interaction with the liner if present). In this study, we report a unique, first of its kind data set of the in situ sampled pore waters of the Boom Clay at the Mol site, covering a depth interval of 65 m. The thorough screening of the collected data for potential geochemical perturbations and sampling artifacts led to a reference data set of 195 pore waters complemented with 39 in situ gas and pH analyses. A statistical analysis was applied to this dataset and a reference pore water composition was derived for the Boom Clay pore water at the Mol site. The reported ranges of the elemental concentrations reflect pore water natural variations at formation scale, whereas in situ sampled pCO2 and pH values are limited to the depth interval enveloped by HADES URL at 196–200 m below sea level. Thus, uncertainty remains on the variations of the pCO2 and pH at the scale of Boom Clay Formation. The reference pore water chemistry dataset will help to update current geochemical pore water chemistry model. At the same time, the presented data set can improve geochemical modelling strategies developed for low permeability sediments, like argillites and shales, where direct pore water sampling is technically difficult. Graphical abstract: Image 1 Highlights: In situ sampled pore waters and dissolved gasses from the underground research lab. CO2 and pH in line with the geochemical model. Isotopic composition of the CO2 gas points to organic matter origin. Reference pore water composition of the Boom Clay at the Mol site.